Style and Structure in Gracián's El Criticón - Welles, Marcia L. (Book collections on Project MUSE., 1976)
This book studies the stylistic importance ofEl Discretoas a prelude toEl Criticonand analyzes the thematic and structural unity of the novel. Special attention is devoted to the elements of allegory and satire, the diversity of their presentation and integration in the narration, and their linguistic dynamism.